Clinical significance of nonhabitual seizures during intracranial EEG monitoring. Issue 1 (2nd December 2013) - Kovac, Stjepana; Rodionov, Roman; Chinnasami, Suganthi; Wehner, Tim; Scott, Catherine A.; McEvoy, Andrew W.; Miserocchi, Anna; Diehl, Beate
Summary This study sought to determine the frequency and clinical significance of nonhabitual seizures in 101 consecutive patients undergoing presurgical intracranial electroencephalography intracranial (icEEG) recording. We compared clinical data, recording details, and postsurgical outcome in patients with nonhabitual seizures to those without nonhabitual seizures during icEEG. In patients with nonhabitual seizures we compared icEEG recordings of nonhabitual seizures to recordings of habitual seizures. Nonhabitual seizures were recorded in 10% of patients. Those patients had a significantly higher rate of procedure‐related complications compared to patients without nonhabitual seizures. Ultimate seizure outcome did not differ between the groups. Nonhabitual seizures often occurred within the first 3 days of icEEG recording and had larger seizure‐onset zones compared to the patient's habitual seizures. Nonhabitual seizures have no effect on outcome of epilepsy surgery but may serve as important markers of procedure‐related complications during icEEG.